Pelatihan Penggunaan Lidah Buaya (Aloe vera) sebagai Foot Crack Cream pada Kader PKK Kelurahan Banmati Sukoharjo - Sa'ad, Muhammad; Setiawan, Iwan (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: Sukoharjo is an area in Central Java that experiencing drought due to the recent hot weather. Meteorology, Climatology and Geophysics Agency shows the average temperature in Sukoharjo between 37-390C with air humidity around 30-50% during the day. This includes Banmati sub-district. Central Statistics Agency also shows rainfall between May-August: 0mm. Extreme hot weather can have a negative impact on skin health. It makes the skin scaly, itchy, dry and cracked due to dehydration. Increased production of oil and sweat due to heat can cause acne and sweat pools by clogging pores. The aim of this service is to provide skills to PKK cadres in Banmati Village, Sukoharjo District, Sukoharjo Regency in making cracked foot cream using natural ingredients, aloe vera. This is done to prevent cracked foot skin disease. Method: The activity began with counseling about skin diseases and the use of natural ingredients to make cream, then continued with practice of making cracked foot cream from Aloe vera. Cadres succeeded in producing cracked foot cream products. Evaluation of service activities is carried out through pre and post-test assessments by each participant to see the increase of cadres' knowledge of skin diseases and the use of aloe vera to make cream. Results: The average pre-test score was 80.86 and post-test was 89.43. There was a significant increase in cadre knowledge after implementing the extension activities (p value 0.000). Conclusions: With the increasing knowledge and ability to make cream, it is hoped that the cadres can provide training to their respective neighborhood circles.